Traditional vs. Modern Human Resource Management: Typology, Transformation, and Industry 4.0 Implications - Meutia Dwi Novita Sari; Raisa Ullya Nisva; M. Rizki Maulana (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2025)
For more than three decades, human resource management (HRM) has evolved from an administrative function geared toward payroll, compliance, and record keeping into a strategic, evidence-based capability that shapes organizational performance and long-term competitiveness. This paper examines the differences between traditional and modern HRM, the field’s development, and transformation mechanisms in the Digital/Industry 4.0 era. This study adopts a qualitative, descriptive approach. Core concepts include HRM logics, e-HRM/HRIS and people analytics, and Industry 4.0. We propose a four-dimension typology (value logic, operating model, data/technology, metrics/decision rights) and a staged pathway (digitalization → standardization → analytics → strategic partnering). Enablers are data governance, analytics capability, and HR–business partnership; a key risk is technology without process redesign. Implications guide organizations and policymakers on sequencing, ethics, and outcome-based metrics.